2019
DOI: 10.9740/mhc.2019.05.128
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil-induced QTc prolongation: A case report

Abstract: Background Several psychoactive medications are known to cause QTc prolongation. Patient factors also increase the risk for QTc prolongation, including bradycardia, female sex, older age, metabolic abnormalities, and polypharmacy. Donepezil, a cholinesterase inhibitor, prolongs the QTc interval through a multimodal mechanism. Patient History A 26-year-old African American female was admitted to the inpatient psychiatric hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Including this initial report, ten cases of QT c prolongation with donepezil were identified, of which five had clearly identified episodes of TdP. 33 , 49 , 52 58 Salient features of these cases are summarised in Table 2 . Eight of the ten cases were in women and two in men.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Including this initial report, ten cases of QT c prolongation with donepezil were identified, of which five had clearly identified episodes of TdP. 33 , 49 , 52 58 Salient features of these cases are summarised in Table 2 . Eight of the ten cases were in women and two in men.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of affected individuals was 77.3 ± 5.8 years (mean ± SEM). However, one case was an outlier 58 in the respect that it involved a young woman (26 years) treated with donepezil for cognitive rehabilitation rather than for AD. The mean age of the nine AD patients receiving donepezil was 83 ± 1.4 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all patients were on multiple medications, nor did all patients have comorbidities. 69,[88][89][90][91][92] Of the four donepezil cases, two cases had minimal comorbidity or polypharmacy relative to other cases, 69,88 perhaps making donepezil more likely to be causally associated with the QT C prolongation and arrhythmia (relative to the other cases). For the Vogel et al case, 92 donepezil was also considered the likely cause of the observed QT C prolongation, in spite of the existing comorbidities and polypharmacy.…”
Section: A Review Of Case Reportsmentioning
confidence: 99%
“…Importantly, the Vogel et al case was the only one we found occurring in a young individual. 92 Findings also worth highlighting include one case having observations of complete atrioventricular block, bradycardia, and ventricular tachyarrhythmia, 69 as well as a case with findings of low heart rate concurrently with premature ventricular contractions 89 (premature ventricular contractions are concerning when in combination with bradycardia 32 ).…”
Section: A Review Of Case Reportsmentioning
confidence: 99%